Simulation of Single Phase Five-Level Inverter Based Modified Pulse-Width Modulation Approach - Maharmi, Benriwati; Ermawati, Ermawati (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
The solar cells can generate electrical energy in form of Direct Current (DC). Generally, electrical appliances have used an Alternating Current (AC). Sequence, an inverter circuit is needed to convert electrical energy form DC to AC. This paper aim is to simulate an inverter performance of single-phase five-level using the method of modified Pulse Width Modulation (PWM). A scheme of the circuit model of single-phase five-level inverter was constructed to investigate their performance. The model was simulated by using of PSIM Software. The simulation parameters were set as a triangular wave frequency used 2 KHz. Then, the same phase was set as the carrier waves and a sinusoidal signal with a frequency of 50 Hz as a reference signal. The circuit scheme model used a switching frequency MOSFET gate as a power switch on the single-phase five-level inverter. The result indicated the simulation as an expectation to generate a constant of five level voltage and sinusoidal current output, which the harmonics values were small. Therefore, the inverter circuit scheme is safe to use for the AC electrical appliances.